Surgical site infection surveillance in orthopedic patients in the Military Medical Academy, Belgrade - Starčević, Srđan; Munitlak, Staša; Mijović, Biljana; Mikić, Dragan; Šuljagić, Vesna (Vojnosanitetski pregled, 2015)
Background/Aim. Active surveillance is an important component of surgical site infection (SSI) reduction strat-egy. The aim of this study was to analyze and compare SSI surveillance data in orthopedic patients in the Military Medical Academy (MMA), Belgrade. Methods. A 4-year prospective cohort study was performed to identify the in-cidence rate and risk factors for SSI in orthopedic patients in the MMA, Belgrade. We collected data regarding pa-tients characteristics, health care and micro-organisms iso-lated in SSI. The National Nosocomial Infection Surveil-lance (NNIS) risk index was subsequently calculated for each patient. The Centers for Disease Control and Preven-tion criteria were used for the diagnosis of SSI. Results. Assessment of 3,867 patients after different orthopedic operations revealed SSI in 109 patients. The overall incidence rate of SSI was 2.8% with the decrease from 4.6% in 2007 to 1.6% in 2010. Using NNIS risk index for surgical procedures there were: 53.7% (2,077) patients with risk 0 – the incidence rate of 1.4%; 38.9% (1,506) patients with risk 1 – the incidence rate of 3.1%; 7.3% (281) patients with risk 2 – the incidence rate of 11.7%; 0.1% (3) patients with risk 3 – without infection within the risk. Multivariate logistic regression analysis identified 6 independent risk factors associated with SSI: contaminated or dirty wounds, smoking, preoperative infection, NNIS risk index, body mass index and the length of hospital stay. Conclusion. The results of our study are valuable confirmation of relations between risk factors and SSI in orthopedic patients. A decreasing incidence rate of SSI (from 4.6% to 1.6%) during a 4-year active surveillance approved its implementation as an important component of SSI reduction strategy.